Prevalence of SARS-CoV-2 and co-infection with malaria during the first wave of the pandemic (the Burkina Faso case) - López-Farfán, Diana; Yerbanga, R. Serge; Parres-Mercader, Marina; Torres-Puente, Manuela; Gómez-Navarro, Inmaculada; Sanou, Do Malick Soufiane; Yao, Adama Franck; Bosco Ouédraogo, Jean; Comas, Iñaki; Irigoyen, Nerea; Gómez-Díaz, Elena (Frontiers in Public Health, 2022)
Africa accounts for 1.5% of the global coronavirus disease 2019 (COVID-19) cases and 2.7% of deaths, but this low incidence has been partly attributed to the limited testing capacity in most countries. In addition, the population in many African countries is at high risk of infection with endemic infectious diseases such as malaria. Our aim is to determine the prevalence and circulation of SARS-CoV-2 variants, and the frequency of co-infection with the malaria parasite. We conducted serological tests and microscopy examinations on 998 volunteers of different ages and sexes in a random and stratified population sample in Burkina-Faso. In addition, nasopharyngeal samples were taken for RT-qPCR of SARS-CoV-2 and for whole viral genome sequencing. Our results show a 3.2 and a 2.5% of SARS-CoV-2 seroprevalence and PCR positivity; and 22% of malaria incidence, over the sampling period, with marked differences linked to age. Importantly, we found 8 cases of confirmed co-infection and 11 cases of suspected co-infection mostly in children and teenagers. Finally, we report the genome sequences of 13 SARS-CoV-2 isolates circulating in Burkina Faso at the time of analysis, assigned to lineages A.19, A.21, B.1.1.404, B.1.1.118, B.1 and grouped into clades; 19B, 20A, and 20B. This is the first population-based study about SARS-CoV-2 and malaria in Burkina Faso during the first wave of the pandemic, providing a relevant estimation of the real prevalence of SARS-CoV-2 and variants circulating in this Western African country. Besides, it highlights the non-negligible frequency of co-infection with malaria in African communities.